Assessment of the main sources of green-house gas emissions in the Waste sector in the Republic of Belarus - Poloz, Irina; Rodkin, Oleg (Journal of the Belarusian State University. Ecology, 2025)
The article presents an assessment of the main sources of greenhouse gas emissions in the «Waste» sector in the Republic of Belarus in the context of global climate change and its impact on the environment. The relevance of this study is determined by the growing problems associated with waste management, as well as the necessity to reduce greenhouse gas emissions to achieve climate goals established by international agreements. From 1989 to 2019, the average annual temperature in the country increased by 1.3°C. Predictions from Belarusian scientists forecast a further temperature rise of 1–5°C by the end of the century. Belarus, as a party to the UN Framework Convention on Climate Change (UNFCCC), the Kyoto Protocol, and the Paris Agreement, has committed to reducing greenhouse gas emissions by 28% by 2030 compared to 1990 levels. The “Waste” sector is a significant source of greenhouse gases, related to the processes of disposal, recycling,and landfilling of large volumes of waste generated by human activities. It has been established that the main sources of greenhouse gas emissions in this sector are solid municipal waste landfills and wastewater treatment facilities. This sector accounts for 32.76% of the total national methane (CH4) emissions and 4.17% of nitrous oxide (N2O) emissions. The total volume of greenhouse gas emissions in the «Waste» sector in 2020 amounted to 5,829.72 Gg in CO2-equivalent, which constitutes 6.56% of the total emissions in the country. The results obtained highlight the importance of developing effective waste management strategies to reduce greenhouse gas emissions and minimize their impact on the climate system.